Analisis Finansial Usaha Perikanan: Studi Kasus Pada Pokdakan Agromino Kelurahan Kramat Utara - Jalunggono, Gentur; Jailani, Abdul Qadir; Aji, Muhammad Tri (Lingka Ekonomika, 2025)
This research is the first year of research with the specific objective of examining the financial analysis of the Pokdakan Agromino fishery business in the North Kramat Subdistrict in an effort to maintain the calculation of operational costs, profits and investment to minimize investment losses. In particular, this study aims to: (1) calculate the Net Present Value (NPV) of the Pokdakan Agromino fishery business in North Kramat Village; (2) Calculating the Internal Rate of Return (IRR) for the fishing business of Pokdakan Agromino, North Kramat Village; (3) Calculating the Payback Period (PP) of the Pokdakan Agromino fishing business in North Kramat Village; and (4) Calculating the Profitability Index (PI) of the Pokdakan Agromino fishing business in North Kramat Village. This research is very urgent to be carried out in order to protect the sustainability of the Pokdakan Agromino fishery business in the Kramat Utara Village and to support efforts to meet the needs for fish food for the people of Magelang City.